2021
DOI: 10.1111/wej.12715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical wastewater treatment using polypropylene membranes incorporated with carboxylated and PEG‐grafted nanodiamond in membrane bioreactor (MBR)

Abstract: The aim of this work is to prepare polypropylene (PP) membrane by embedding carboxylated(-COOH) and also polyethylene glycol(-PEG) functionalized nanodiamond to improve membrane hydrophilicity and decline membrane fouling in pharmaceutical wastewater treatment. Porosity, contact angle, mechanical strength, field emission scanning electron microscopy (FESEM) and membrane pure water permeation analysis were performed for the characterization of the membranes. The membranes with 0.75 wt.% of nanoparticles introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…7b, which illustrates that the PSF membrane provides the lowest permeate flux (10.57, 11.4, 17.23 L m −2 h −1 ) using feed concentrations of 30, 60, and 120 mg L −1 DCF, respectively. The results confirm that the permeate flux is directly proportional to the membrane hydrophilicity 58, 59. The addition of NP enhances the membrane performance as they facilitate water absorption by the membrane.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…7b, which illustrates that the PSF membrane provides the lowest permeate flux (10.57, 11.4, 17.23 L m −2 h −1 ) using feed concentrations of 30, 60, and 120 mg L −1 DCF, respectively. The results confirm that the permeate flux is directly proportional to the membrane hydrophilicity 58, 59. The addition of NP enhances the membrane performance as they facilitate water absorption by the membrane.…”
Section: Resultssupporting
confidence: 69%
“…The addition of NP enhances the membrane performance as they facili-tate water absorption by the membrane. Moreover, the NP create regular structures due to crystal growth throughout the phase inversion process [59,60]. The PSF/Mn 2 O 3 membrane has the highest removal rate and permeate flux at a feed concentration of 30 mg L -1 .…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Recently, the development of new antifouling materials has involved complex synthesis of additives. Some studies combine two sets of additives and blend them together into the polymeric matrix [ 81 , 289 , 350 , 351 , 352 , 353 , 354 ] to improve both antifouling properties and photocatalytic activities of the prepared membranes. However, this should be carried out with great consideration with regards to the ensuing thermodynamics instability of the system, and how this could also influence the viscosity and kinetics of the phase separation.…”
Section: Antifouling Materials For Polymeric Membranesmentioning
confidence: 99%
“…Raeiszadeh et al 33 obtained NDs with high carboxyl content through air oxidation, improved the degree of dispersion, and doped them into the chitosan to effectively improve the adsorption capacity of methyl orange. Hosseinpour et al 34 investigated the properties of polypropylene membranes prepared by pegylated functionalized NDs in MBR, which has improved the treatment of pharmaceutical wastewater. Vatanpour et al 35 prepared PES membranes doped with explosive NDs, which showed high removal rates for reactive green 19 and reactive orange 29 in terms of dye separation.…”
Section: Introductionmentioning
confidence: 99%